Novel QuEChERS-ultra-performance liquid chromatography–atmospheric-pressure chemical ionization tandem mass spectrometry method for the simultaneous determination of vitamin D and vitamin K in vitamin-fortified nanoemulsions. (30th September 2022) - Kim, Tae-Eun; Yoo, Guijae; Hyeock Lee, Min; Kim, Bum-Keun; Won Jang, Hae
Highlights: A technique to determine vitamin D and K content in vitamin-fortified nanoemulsions. QuEChERS method was optimized by response surface methodology. UHPLC-APCI-MS/MS was used to determine vitamins D and K levels. The proposed method exhibited excellent selectivity, precision, and accuracy. Simultaneous analysis of vitamins D2, D3, K1, and K2 could be realized in vitamin-fortified yogurt. Abstract: Nanoemulsion is a new vehicle for food fortification. In this study, a simple and reliable method for the simultaneous analysis of vitamins D2, D3, K1, and K2 in vitamin-fortified nanoemulsions was developed using QuEChERS (quick, easy, cheap, effective, rugged, and safe) extraction and ultra-high performance liquid chromatography–atmospheric-pressure chemical ionization tandem mass spectrometry techniques. Response surface methodology was employed to optimize the extraction parameters. The method was validated for the vitamins in terms of LOD (0.03–0.25 μg/L), LOQ (0.10–0.77 μg/L), intra-day (≤4.50%), inter-day precisions (≤6.43%), and accuracy (98.5%–108.0%). The recoveries of the vitamin-fortified nanoemulsion and yogurt were in the ranges of 104.0%–109.2% and 73.3%–85.2%, respectively. The solvent consumption and analysis time were reduced by 5.6 and 3.3 folds, respectively, rendering it superior to the traditional extraction methods established by the Association of Official Analytical Chemists and the Ministry of Food and Drug Safety.